PEMANFAATAN INSTAGRAM @PINALOKA.ID SEBAGAI MEDIA SOSIAL MARKETING USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DALAM MEMBANGUN BRAND AWARENESS DI KABUPATEN SIAK - Agassi, Salsabila; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study discusses the utilization of Instagram as a social marketing media for UMKM Pinaloka in an effort to build brand awareness in Siak Regency. UMKM Pinaloka is a business group that produces local pineapple processed products as superior products based on village potential. Before utilizing social media, UMKM Pinaloka marketing was conventional and geographically limited, along with the development of digital technology, Instagram was chosen as the main platform to expand market reach and increase brand awareness effectively. This study aims to analyze how the use of Instagram @pinaloka.id.id as a social media marketing for MSMEs in building Brand Awareness in Siak Regency. This study uses a qualitative method with a descriptive approach and to determine informants, namely by using a purposive technique. Data collection techniques in this study used interviews, observations, and documentation. This study uses the theory of Social Media Marketing and the concept of The Circular Model of SOME created by Regina Luttrel which has 4 stages, namely Share, Optimize, Manage, Engage. The results of the study show that at the Share stage, @pinaloka.id actively shares educational visual content and product promotions based on local narratives. At the Optimize stage, Instagram accounts are managed with consistent posting, hashtag utilization, and insight monitoring, at the Manage stage, @pinaloka.id carries out account management in a structured manner, is responsive to the audience, and routinely monitors interaction activities, while at the Engage stage, engagement is built through collaboration with influencers, event organizers, and the use of usergenerated content. The integrated use of SOME has been proven to increase brand visibility, expand market reach, and strengthen emotional relationships between consumers and brands. These findings confirm that Instagram can be an effective tool in digital transformation and strengthening the position of MSMEs in the era of a technology-based economy.MSMEs in the era of a technology-based economy.